Sastra Lisan pada Mantra Pengobatan Tradisional di Cibaliung Banten - Trisnawati, Trisnawati (Jurnal Artikula, 2024)
This study aims to examine the meaning and function of mantras in the Cibaliung Pandeglang Banten area. The study conducted by the researcher includes what meanings are contained in the mantras and what functions are in the mantras. Meaning is a description of the mantras that indirectly provide messages to us as readers and those who preserve them, especially the people in Cibaliung village. Mantras also function to provide solutions or ways out when people experience obstacles in their lives. The method used is a descriptive qualitative method, namely analyzing mantras in their meaning and function, and the author conducts interviews with informants who have these mantras. Thus, the research will be objective and the author obtains relevant data.